A comissão municipal de monitoramento e avaliação do plano municipal de educação de Ponta Porã-MS: desafios, perspectivas e consolidações - Barcelos, Fabiany dos Santos (2023)
This Doctoral Thesis analyzes the performance of the Municipal Monitoring and Evaluation Commission (CMMA) of the Municipal Education Plan (PME) of Ponta Porã-MS, in terms of challenges, perspectives and consolidations during the period between 2015 and 2022. The study is associated with the Research Line ‘Policies and Education Management', of the Postgraduate Program in Education (PPGEdu), of the Faculty of Education (FAED), of the Federal University of Grande Dourados (UFGD) and is a result of the Collaborative Research Project (2017) entitled 'Monitoring of Municipal Education Plans (PMEs) of the State of Mato Grosso do Sul (MS)', subsidized by FUNDECT. The problematization of the research was systematized by the following question: how was the performance of the Municipal Monitoring and Evaluation Commission of Ponta Porã during the monitoring and evaluation process of the Municipal Education Plan/Ponta Porã (2015-2025), in terms of challenges , perspectives and consolidations? This is a qualitative research with a bibliographic, documentary and field-based approach. The field research took place through the application of semi-structured interviews and an online questionnaire with the participants of CMMA/Ponta Porã. Considering the analyzes undertaken, the thesis is that the performance of CMMA/PME-Ponta Porã-MS in the monitoring and evaluating process of PME/Ponta Porã, conducted by CMMA, has shown progress regarding the organization of the commission, document elaboration and goal achievement, demonstrating progress in local educational planning policy. The data show that, although the PME/Ponta Porã Municipal Monitoring and Evaluation Commission has been committed to its functions, the local scenario still indicates lfew advances concerning the consolidation of the Municipal Education Plan, as the challenges revealed difficulties in PME monitoring and evaluation processes, such as the absence/outdated of data, lack of coordination among the organizations involved in the process, limited participation of civil society in debates and mobilizations, lack of investment and discontinuity of public educational policies. In summary, the research indicates that the CMMA of Ponta Porã presents an instrumental participation in the PME monitoring and evaluation process, rather than an active and political participation aimed at promoting social control of educational policy. Through this study, the aim is to collaborate with the strengthening of educational planning in the municipality of Ponta Porã/MS, in compliance with the PME, Law N. 4.100, of June 2, 2015, as well as to contribute to research on the evaluation and monitoring of the Deccenial Education Plans.